Importancia de la dactiloscopia en la comisión del delito de hurto (2014)
In our country, the activities of criminal investigation, are known as judicial police, because they are under strict judicial control; considering whether the search and collection of physical and identification of this evidence, properly performed; seeks to reach the primary purpose of the criminal investigation, which is to find a causal link between the actors of the criminal offense and the scene. When the investigators of the Judicial Police are faced with the typical behavior punishable theft, carried out first setting the scene and then proceed to choose the appropriate search method in order to obtain lofocopicas evidence; it is essential that these are collected at the scene, packaged and labeled in the prescribed manner, so that when these are sent to laboratories for the corresponding study Dijin; produce effective results in the end we lead actors of the conduct under investigation. The expert witness in fingerprinting analyzes the physical evidence collected at the scene where the incident occurred, so that they can provide information to identify those suspected of committing the conduct typified actors and thus to initiate appropriate judicial proceedings